Pollen Morphology and Sucrose Giving on Stigma Relation with Incompability of Sweetpotato (Ipomoea batatas (L.) L.) - Febri Adi Susanto; Eko Sri Sulasmi; St A Rahayuningsih (Journal of Tropical Life Science, 2013)
The purpose of the research is to examine how to increase cross and self-pollination by solving incompatibility of sweet potato mechanism through sucrose giving on stigma and pollen nuclei checking. Sucrose in different concentration is giving to stigma. Stigma is excised and lubricated with sucrose before crossing and the pedicel is lubricated with 2,4D 100 ppm in lanolin. The result shows both varieties have stigma position longer than the anthers do. Papua Solosa has 94.7% anther dehiscence, 70.25% pollen viability, while MSU 03028-10 has 87.3% anther dehiscence and 87.84% pollen viability. Both of these varieties have receptive stigma. Sucrose level in compatible pollination is lower than in incompatible pollination. Sugar in 50 ppm concentrate can increase fruit setting in self-pollination of Papua Solosa variety from 0% to 70%, 0% to 60% in MSU 03028-10, and 10% to 90% in crossing of Papua Solosa>Keywords : Pollen Morphology, Sucrose Giving, Incompatibility of Sweet Potato